EVALUASI PENERAPAN SISTEM LAYANAN ADMINISTRASI KEPENDUDUKAN DI KOLAKA UTARA - Khatimah, A Khusnul; Usman, Jaelan; Wardah, Wardah (Universitas Muhammadiyah Makassar, 2024)
This research aims to determine the evaluation of the implementation of the population administration service system at the population and civil registration service in North Kolaka Regency. Using the research method is qualitative research with a qualitative descriptive type. The informants in this study were 5 people. The process of searching and compiling data is obtained from observations, interviews and documentation. The results of this research show that: 1). Effectiveness, the implementation of Si LAKU O2T in terms of service quality in dukcapil has been effective for several services, but there will be a decrease in the number of services in 2023. 2). Efficiency, the implementation of Si LAKU O2T has not been effective and efficient overall, and dukcapil provides services offline and online. 3). The adequacy and completeness of the available facilities is not yet available, but the data availability is available and accurate because it is recorded in the SIAK application. 4). Equality, all people get the same service and feel satisfied 5). Responsiveness, Si LAKU O2T has a good response to data changes. 6). Accuracy, information regarding Si LAKU O2T is accurate and well conveyed to thepublic.